2007
DOI: 10.1177/0093854806296039
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Level of Service Inventory—Revised (LSI-R) Among African American and Hispanic Male Offenders

Abstract: The Level of Service Inventory-Revised (LSI-R) is a dynamic risk/needs assessment instrument that has been used extensively among a variety of offender samples. Validity research on the LSI-R, however, is based on samples consisting predominantly of Caucasian participants. The present study sought to examine the psychometric properties and validity of the instrument among a sample of African American and Hispanic male offenders. Participants were 446 male parolees residing in three halfway houses and one day r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 18 publications
2
59
0
Order By: Relevance
“…This finding merits further investigation, particularly given the high incidence of Aboriginal offenders under the agency's authority. Other studies have produced mixed results, with some not finding a decrement in predictive validity among Aboriginal offenders for this (Gossner & Wormith, 2007;Rector et al, 2007) or other versions of the Level of Service Inventory (Bonta, LaPrairie, & Wallace-Capretta, 1997), whereas other studies have found a decrement in predictive validity among Native American offenders and other ethnic minorities on LSI-R (e.g., Holsinger et al, 2006;Schlager & Simourd, 2007).…”
Section: Predictive Validitymentioning
confidence: 99%
“…This finding merits further investigation, particularly given the high incidence of Aboriginal offenders under the agency's authority. Other studies have produced mixed results, with some not finding a decrement in predictive validity among Aboriginal offenders for this (Gossner & Wormith, 2007;Rector et al, 2007) or other versions of the Level of Service Inventory (Bonta, LaPrairie, & Wallace-Capretta, 1997), whereas other studies have found a decrement in predictive validity among Native American offenders and other ethnic minorities on LSI-R (e.g., Holsinger et al, 2006;Schlager & Simourd, 2007).…”
Section: Predictive Validitymentioning
confidence: 99%
“…Two of the most widely used risk assessment instruments in North American correctional agencies are the Level of Service Inventory-Revised (LSI-R) and the Youth Level of Service/Case Management Inventory (YLS/CMI). While extensive psychometric research has been conducted on these two tools to demonstrate validity with much of the results suggesting the tools have adequate accuracy (see e.g., Schlager & Simourd, 2007;Schmidt, Hoge, & Gomes, 2005;Smith, Cullen, & Latessa, 2009), there is a relative dearth in the literature regarding reliability.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers suggest that the LSI-R may not accurately classify non-White offenders (Holsinger et al, 2003(Holsinger et al, , 2006Whiteacre, 2006), but these findings are far from conclusive. Moreover, most researchers who have investigated the predictive validity of the LSI-R across offender racial and ethnic groups relied on samples drawn from community settings but not prison settings (e.g., Fass et al, 2008;Schlager & Simourd, 2007;Whiteacre, 2006). …”
mentioning
confidence: 99%